Ordered patterns formed on polymer film through trapping and locking. Issue 24 (14th September 2015) - Lin, Ligang; Wang, Yuanyuan; Sun, Hui; Zhang, Chao; Zhong, Yonghui; Zhang, Yuzhong
ABSTRACT: Polymer films with ordered patterns have attracted considerable interest because of their potential applications. Herein, an innovative and facile strategy for patterned film formation by means of a trapping and locking process has been proposed. The results demonstrated that within seconds periodic structures with hexagonal packing could be obtained without the use of a template. Quite a few common polymers could be implemented in this novel fabrication method. Solvent evaporation and nonequilibrium convection have been determined to be responsible for the formation of ordered patterns that are fixed and locked on the film's surface through a simple solidification step. It is remarkable that the nonequilibrium convection and the polymer's architecture on the molecular scale could be trapped on a macroscopic scale. The straightforward strategy disclosed herein has general suggestions for the molecular structure transcription and the pattern formation techniques. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2015, 53, 1701–1705 Abstract : An innovative trapping and locking strategy for patterned film formation was proposed. Periodic structures with hexagonal packing are obtained without any templates within several seconds. Nonequilibrium convection and the ring structure sequences in the polymer play significant roles. The convection and architecture at the molecular scale are trapped at a macroscopic scale. The strategy has general implications for molecular structure transcription.